(untitled) (Research, Society and Development, 2021)
Smart cities improve their mass transportation system through their diversified offering of urban modes of transportation for public transport. There are options of smart and sustainable technologies that can be embedded and available to be used in this system. The composition of the urban mass transportation system is a public/private and consortium service offered to a demand from citizens that aims to improve urban mobility. Urban mass transport can be classified based on data such as the types of existing mass transport modes, the smart technologies available, and the energy sources used for locomotion. In this research, the multiple case study method of the mass transportation system was applied, with the use of the triangulation technique of three databases collected in 2020. The aim of this study was to analyze and understand the composition and concentration of urban mass transport systems in four smart cities with metropolitan profile and classify these smart cities using reports and dashboards with the aid of Power Business Intelligence (BI) software from Microsoft as the ultimate analysis tool. It is considered that these metropolitan urban mass transportation systems are historically built-in stages of technological evolution and are deployed in smart cities according to the urban mobility needs of the cities, and can be classified as more or less diverse, more or less technological, and more or less clean or polluting.